2020
DOI: 10.21037/atm-20-5222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radioactive iodine treatment on cardiovascular disease in thyroid cancer patients: a nationwide cohort study

Abstract: Background: Radioactive iodine (RAI) treatment is a standard treatment in differentiated thyroid cancer (TC). However, its adverse effects on cardiovascular diseases (CVDs) have not been clearly elucidated. Methods:In this retrospective cohort study based on the Korean National Health Insurance Service-National Health Screening Cohort (2002Cohort ( -2015, we analyzed 4,845 patients with TC with a median followup of 66 months. We evaluated and compared the risk of CVD between patients treated with and without R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Of the 41 studies, 23 ( N = 1,972,059) reported the incidence of ischemic stroke events at 1 year after a diagnosis of cancer ( 13 15 , 17 , 18 , 20 , 25 , 26 , 30 , 34 – 36 , 39 49 ). The pooled incidence of ischemic stroke events during the first year after a new diagnosis of cancer (see Figure 3 ) was 1.3% (95% CI 1.0–1.8%) with a high degree of statistical heterogeneity present ( I 2 = 99.72%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 41 studies, 23 ( N = 1,972,059) reported the incidence of ischemic stroke events at 1 year after a diagnosis of cancer ( 13 15 , 17 , 18 , 20 , 25 , 26 , 30 , 34 – 36 , 39 49 ). The pooled incidence of ischemic stroke events during the first year after a new diagnosis of cancer (see Figure 3 ) was 1.3% (95% CI 1.0–1.8%) with a high degree of statistical heterogeneity present ( I 2 = 99.72%).…”
Section: Resultsmentioning
confidence: 99%
“…There were 11 studies ( N = 1,361,817) that reported the incidence of ICH at 1 year after a diagnosis of cancer ( 14 , 15 , 17 , 18 , 20 , 25 , 26 , 30 , 34 , 50 , 51 ). The pooled incidences of ICH at 1 year after diagnosis was 0.3% (95% CI 0.1–0.9%) with a high degree of statistical heterogeneity present ( I 2 = 99.46%) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a study on the safety of RAI treatment reported that the incidence of leukemia significantly increased (HR, 3.1) in patients who received a cumulative dose of 100 mCi or more, and this has emerged as a major issue [56]. No association was reported between RAI treatment and the occurrence of long-term CVD [57]. In addition, studies on mortality [58,59] and second primary malignancies [60,61] were conducted to obtain insights into the long-term prognosis of thyroid cancer, and cases of simultaneous or sequential occurrence of thyroid cancer and breast cancer were reported [62].…”
Section: Article In Pressmentioning
confidence: 99%
“…Lin et al [34] retrospectively evaluated the association between I-131 therapy for TC and stroke risk in 10,104 Taiwanese DTC survivors (mean age 49.4 years). The participants were classified into two groups that did and did not receive I-131 therapy.…”
Section: Association Between I-131 Therapy and Cardiovascular/cerebrovascular Morbiditymentioning
confidence: 99%